Ministry Of Finance Decree No. 333 For The Year 2018 Amending Certain Provisions of the Minister of Finance's Decree No. 525 of The Year 2006 Issuing the Executive Regulations of the Stamp Duty Law Promulgated by Law No. 111 of the Year 1980 = وزارة المالية قرار رقم 333 لسنة 2018 بشأن تعديل قرار وزير المالية رقم 525 لسنة 2006 بإصدار اللائحة التنفيذية لقانون ضريبة الدمغة الصادر بالقانون رقم 111 لسنة 1980 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic